URGENSI BIMBINGAN KARIER DALAM MENINGKATKAN PENGETAHUAN KARIER PESERTA DIDIK DI MAN 1 BANDAR LAMPUNG - Tri Diyah Lestari; Nurus Sa'adah (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2021)
The confusion experienced by learners in determining career continuity due to a lack of knowledge of the acquired career is the underlying problem of this research. This research aims to how the implementation of career guidance and its importance of it in increasing the career knowledge of learners at MAN 1 Bandar Lampung. Researchers use qualitative research methods in the form of field research, which is descriptive. The data source in this study is 3 BK personnel and 6 learners who are certainly actively participating in career guidance activities. As for the data collection technique in this study, namely with observation methods, interviews, and documentation. Then for data analysis used is an interactive analysis of milles and Huberman models consisting of data reduction steps, presentation of data, and withdrawal of conclusions. Based on the results of research shows that the implementation of career guidance in improving career knowledge at the beginning of the stage of material preparation, information services, and evaluation. Increasing the career knowledge of learners makes them able to plan and take steady career decisions.